La réforme de la responsabilité médicale : responsabilité ou assurance ? - Baudouin, Jean-Louis (Assurances, 1992)
The author, the general reporter of the 13th Congress of the International Academy of Comparative Law, held in Montréal from August 19 to August 24, 1990, presents a two-part study on the current law of medical responsibility as viewed by the participating countries. In the first part, Mr. Baudouin analyzes different systems of responsibility, looks at third party liability which is most often invoked in the case of medical assistants who also act under the order of doctors or hospitals and the responsibility for malpractice resulting from health care technology, a problem caused by the growing reliance on technology for diagnosis and treatment. We only publish the second part of Mr. Baudouin’s text which presents a comparative study on two insurance models for legal compensation: Sweden and Finland.